KAJIAN LITERATUR MENGENAI PEMANFAATAN BAHAN ALAM SEBAGAI FLOKULAN UNTUK PEMANENAN CHLORELLA VULGARIS - SYLVA HUTASOIT; INDRA PANGGABEAN; NINA JULIANA ROBERTA TURNIP; ASTITI ADITIA (LP2MTBM MAKARIOZ, 2020)
Research studies on microalgae such as Chlorella vulgaris have been widely carried out because they can be used invarious field. Chlorella vulgaris is a promising source of raw materials for oil, food, animal feed, pharmaceuticals, cosmeticproducts and high-value products. However, their use is hindered by the large volume harvesting process. Flocculation isseen as a cheap and promising harvesting method as a technique for harvesting microalgae to obtain large amounts ofbiomass. Metal salts such as alum and ferric chloride are commonly used as flocculants in the microalgae harvestingprocess. However, its use creates metal residues on the harvested biomass, so that other solutions are sought to obtainflocculants. Natural flocculants derived from natural ingredients need to be studied and developed their potential forharvesting microalgae. Apart from being environmentally friendly compared to chemical flocculants, another advantage isthat it is abundant in nature and renewable. Among natural flocculants, corn kernels, chitosan, Moringa oleifera seeds andcellulose have been developed through several studies related to their use as flocculants. The results obtained were thatnatural flocculants were able to reduce turbidity, anionic surfactants and other colloidal particles in water treatment usingflocculation techniques. However, it needs to be further reviewed regarding its use in the flocculation process of Chlorellavulgaris by considering several parameters.